A brief review on the mechanical behavior of nonwoven fabrics. (November 2020) - Yilmaz, Korhan Babacan; Sabuncuoglu, Baris; Yildirim, Bora; Silberschmidt, Vadim V
Although nonwovens used in many areas from civil and mechanical engineering to consumer products, research on their mechanical behavior are rather limited in the literature. In this study, a brief overview is presented on the previous research performed to understand the relation between the microstructure and the mechanical behavior of these materials. The research studies are categorized into five sections declining with tensile, creep, bending, dynamic and damage behavior. For each type of behavior, previous research is discussed briefly following by that of the last few years. The review demonstrates that the tensile behavior is understood well whereas there is a limited number of studies in bending and dynamic behavior of nonwoven materials. Future research is expected to be more related on the in-service behavior.